Nasopharyngeal Carcinoma and Its Microenvironment: Past, Current, and Future Perspectives - Su, Zhi Yi; Siak, Pui Yan; Leong, Chee-Onn; Cheah, Shiau-Chuen (Frontiers in Oncology, 2022)
Nasopharyngeal carcinoma (NPC) is an epithelial malignancy that raises public health concerns in endemic countries. Despite breakthroughs in therapeutic strategies, late diagnosis and drug resistance often lead to unsatisfactory clinical outcomes in NPC patients. The tumor microenvironment (TME) is a complex niche consisting of tumor-associated cells, such as fibroblasts, endothelial cells, leukocytes, that influences tumor initiation, progression, invasion, and metastasis. Cells in the TME communicate through various mechanisms, of note, exosomes, ligand-receptor interactions, cytokines and chemokines are active players in the construction of TME, characterized by an abundance of immune infiltrates with suppressed immune activities. The NPC microenvironment serves as a target-rich niche for the discovery of potential promising predictive or diagnostic biomarkers and the development of therapeutic strategies. Thus, huge efforts have been made to exploit the role of the NPC microenvironment. The whole picture of the NPC microenvironment remains to be portrayed to understand the mechanisms underlying tumor biology and implement research into clinical practice. The current review discusses the recent insights into the role of TME in the development and progression of NPC which results in different clinical outcomes of patients. Clinical interventions with the use of TME components as potential biomarkers or therapeutic targets, their challenges, and future perspectives will be introduced. This review anticipates to provide insights to the researchers for future preclinical, translational and clinical research on the NPC microenvironment.